The Correlation Between Mother’s Knowledge Level and Feeding Patterns with the Incidence of Stunting in Toddlers in Puhkerep Village, Nganjuk Regency - NIRWANA, ELINK ALIVIA (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Stunting is a growth and development problem in children caused by malnutrition, infection, and lack of psychosocial stimulation. Stunting can be identified through age-inappropriate body size, which is less than two standard deviations. Factors such as maternal knowledge and feeding patterns influence the incidence of stunting. This study aimed to evaluate the incidence of stunting, maternal knowledge, feeding patterns, and the relationship between maternal knowledge and feeding patterns with stunting in Puhkerep Village, Nganjuk Regency. This study used a quantitative cross-sectional design and involved 74 children aged 1-5 years who were cared for by their biological mothers and lived in Puhkerep Village. The variables studied included maternal knowledge and feeding patterns as independent variables, and the incidence of stunting as the dependent variable. Respondents were selected using accidental sampling technique, and the instruments used included knowledge test, questionnaire, microtoise, and infantometer. Data analysis was conducted using the chi-square test. The results showed a significant relationship between maternal knowledge and the incidence of stunting in toddlers (p value = 0.004) and between feeding patterns and the incidence of stunting (p value = 0.000; OR = 3.169). These findings indicate that low maternal knowledge can increase the risk of stunting, while good feeding patterns can reduce the risk of stunting.